2009
DOI: 10.1063/1.3251783
|View full text |Cite
|
Sign up to set email alerts
|

Thermalization of exciton states in silicon nanocrystals

Abstract: Self-trapped excitons in silicon nanocrystals with sizes below 1.5 nm in Si/SiO 2 multilayers Silicon nanocrystals are studied by time-resolved fluorescence spectroscopy. After laser excitation the bright and dark exciton ground state levels are populated at random, but subsequently the decay curves reveal a thermalization between these levels. The characteristic thermalization time is found to be approximately 100 ns for temperatures below 100 K and surprisingly increases for higher temperatures. The decay cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Importantly, both experimental and theoretical efforts have begun to explore the fine structure of sustainable materials. On the experimental side, the nature of dark and bright exciton states corresponding to spin-allowed and forbidden transitions, respectively, has been investigated with temperature-dependent PL decay measurements for InP/ZnS, 250 ZnSe 251 and Si 252 NCs. Meanwhile, atomistic pseudopotential calculations have investigated the relationship between the magnitude of the bright/dark exciton splitting and the size of GaAs, InAs and Si QDs.…”
Section: Sustainable Future Quantum Technology With Colloidal Ncsmentioning
confidence: 99%
“…Importantly, both experimental and theoretical efforts have begun to explore the fine structure of sustainable materials. On the experimental side, the nature of dark and bright exciton states corresponding to spin-allowed and forbidden transitions, respectively, has been investigated with temperature-dependent PL decay measurements for InP/ZnS, 250 ZnSe 251 and Si 252 NCs. Meanwhile, atomistic pseudopotential calculations have investigated the relationship between the magnitude of the bright/dark exciton splitting and the size of GaAs, InAs and Si QDs.…”
Section: Sustainable Future Quantum Technology With Colloidal Ncsmentioning
confidence: 99%
“…This means, that there must be spin-flip processes involved to reach the thermal equilibrium. Julsgaard et al have directly observed such scattering processes [29] and showed that the scattering time is around 0.1µs, indeed significantly smaller than the photoluminescence decay time.…”
Section: R R (T ) ∝ I (T ) · R Plmentioning
confidence: 97%